2018
DOI: 10.2166/wst.2018.018
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of chitosan/amine modified diatomite composites and adsorption properties of Hg(II) ions

Abstract: A green functional adsorbent (CAD) was prepared by Schiff base reaction of chitosan and amino-modified diatomite. The morphology, structure and adsorption properties of the CAD were characterized by Fourier transform infrared spectroscopy, thermogravimetric analysis, scanning electron microscopy and Brunauer Emmett Teller measurements. The effect of pH value, contact time and temperature on the adsorption of Hg(II) ions for the CAD is discussed in detail. The experimental results showed that the CAD had a larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…It is noticed that the As(Ⅴ) removal efficiency increased rapidly as the adsorbent dosage increased from 0.1 to 0.4 g/L, which may be due to that the active sites for binding target ions on the adsorbent surface was less at a lower dose of adsorbent [54]. When the dosage of the CS-modified Dt was more than 0.4 g/L, the removal efficiency increased relatively slowly, and the adsorption surface of CS-modified Dt might gradually reach the saturation state [35]. Therefore, considering As(Ⅴ) removal and economy, 0.4 g/L is the optimal value of adsorbent dosage.…”
Section: Effect Of Adsorbent Dosagementioning
confidence: 96%
See 1 more Smart Citation
“…It is noticed that the As(Ⅴ) removal efficiency increased rapidly as the adsorbent dosage increased from 0.1 to 0.4 g/L, which may be due to that the active sites for binding target ions on the adsorbent surface was less at a lower dose of adsorbent [54]. When the dosage of the CS-modified Dt was more than 0.4 g/L, the removal efficiency increased relatively slowly, and the adsorption surface of CS-modified Dt might gradually reach the saturation state [35]. Therefore, considering As(Ⅴ) removal and economy, 0.4 g/L is the optimal value of adsorbent dosage.…”
Section: Effect Of Adsorbent Dosagementioning
confidence: 96%
“…In Figure 1b, the peaks at 3697 and 3621 cm −1 are disappeared and the peak at 3432 cm −1 is broadened and enhanced, resulting from overlapping between the N-H and -OH stretching vibrations [27]. Compared to the spectrum of the raw Dt, there is a significant difference, with two new peaks appearing in the spectrum of the CS-modified Dt at 2924 and 1560 cm −1 attributed to -CH 2 -stretching vibration and -NH 2 bending vibration of the CS [34,35]. The peaks at 1635, 1090, and 1383 cm −1 were shifted to 1640, 1093 and 1401 cm −1 , respectively.…”
Section: Desorption and Regeneration Studiesmentioning
confidence: 98%
“…Its porous structure, high specific surface area, rich silicon hydroxyl functional groups on the surface and many active sites endow it with excellent adsorption capacity, especially the electronegativity of the surface, which has an adsorptive effect on cationic pollutants. DE and its modified materials are considered to be a new type of high‐efficiency, environmentally friendly adsorbent 18‐20 . Chao et al 21 .…”
Section: Introductionmentioning
confidence: 99%
“…DE and its modified materials are considered to be a new type of high-efficiency, environmentally friendly adsorbent. [18][19][20] Chao et al 21 used DE with a high specific surface area to adsorb TC. It was found that the material had good adsorption performance for TC, and the adsorption was in accordance with the quasi-second-order kinetic model; adsorption equilibrium was reached in 120 min, and the adsorption was in agreement with the Langmuir isothermal adsorption model.…”
Section: Introductionmentioning
confidence: 99%
“…Diatomite (SiO 2 ⋅ nH 2 O), composed of amorphous silica, is a lightweight, porous natural mineral that originates from the fossilization of small diatom shells. [1] The diatomite shell has excellent properties such as high porosity, low density, high surface area, superior physicochemical stabilities, and mesoporous structure. Due to these advantages, together with the ecofriendly nature, abundant reserves, low price, and separability, diatomite is an excellent support material for the preparation of nanoparticle catalysts.…”
Section: Introductionmentioning
confidence: 99%